1989
DOI: 10.1002/pros.2990140405
|View full text |Cite
|
Sign up to set email alerts
|

Intermediate filament expression and the progression of prostatic cancer as studied in the dunning R‐3327 rat prostatic carcinoma system

Abstract: To evaluate if there is any consistent relationship between the expression of intermediate filament proteins (IFP), particularly keratins, and the degree of malignancy of prostatic cancer cells, a series of nine Dunning rat prostatic cancer sublines that span the entire spectrum of progression of prostatic cancer were studied immunocytochemically by the use of a variety of antibodies specific for keratins, vimentin, or desmin. For the keratin studies, monoclonal antibodies with either a general reactivity to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

1992
1992
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 19 publications
2
9
0
Order By: Relevance
“…Antiandrogens, such as flutamide and cyproterone acetate, also induce ACD in the prostate [69] and in prostate derived tumor cell lines, such as the rat Dunning 3327 H subline [70] and the human PC-82 and PC-EW [71]. LH-RH and flutamide induce ACD in the hormone-dependent R3328H Dunning prostate cell line [72].…”
Section: Ha Hormonal Regulationmentioning
confidence: 99%
“…Antiandrogens, such as flutamide and cyproterone acetate, also induce ACD in the prostate [69] and in prostate derived tumor cell lines, such as the rat Dunning 3327 H subline [70] and the human PC-82 and PC-EW [71]. LH-RH and flutamide induce ACD in the hormone-dependent R3328H Dunning prostate cell line [72].…”
Section: Ha Hormonal Regulationmentioning
confidence: 99%
“…Using cytokeratin polypeptide-specific monoclonal antibodies (MoAbs), different types of epithelia can be distinguished immunohistochemically. Earlier studies have shown that such MoAbs can differentiate between the luminal and basal cell compartments in the normal prostate of man (4), rat (20,26) and calf (27). The purpose of this study was to determine the expression of cytokeratins in diethylstilbestrol dipropionate (DES-DP)-induced hyperplastic and metaplastic lesions in the peripheral glandular epithelium of the goat prostate and to compare this to the normal epithelium.…”
Section: Introductionmentioning
confidence: 99%
“…Object slides were then incubated with the specified antibody (Table I) for 30 min at 37°C at the indicated dilution. We used rabbit anti-mouse peroxidase (DAKO) as secondary antibodies, diluted 1/100 and containing 2% nonimmune rabbit serum and swine anti-rabbit peroxidase (DAKO), diluted 1/100, for acinary epithelium (261 luminal cells [17] squamous epithelium [21] basal cells [27] prostatic glandular epithelium [28] smooth muscle cells [23] muscle cells [supplier]…”
Section: Lmmunostaining Proceduresmentioning
confidence: 99%